Efforts to Improve Student Learning Outcomes by Implementing the Project Based Learning Model in Islamic Education Learning at SD Negeri 2 Baktiya - Muzakkir; Abdullah (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to improve students’ learning outcomes in Islamic Education learning through the implementation of the Project Based Learning (PjBL) model at SD Negeri 2 Baktiya. The research employed a Classroom Action Research (CAR) design conducted in two cycles, consisting of planning, action, observation, and reflection stages. The participants were 28 fifth-grade students. Data were collected through learning outcome tests, observation sheets of student learning activities, and teacher performance evaluation instruments. The results indicated a significant improvement in students’ learning outcomes after applying the PjBL model. In the pre-cycle stage, only 11 students (39.29%) achieved the minimum mastery criterion (MMC), with an average score of 64.21. After the implementation of PjBL in Cycle I, the number of students achieving mastery increased to 18 students (64.29%), with an average score of 72.46. Furthermore, Cycle II showed a more substantial improvement, where 25 students (89.29%) achieved mastery and the class average score increased to 82.14. Observational data also revealed that students’ learning engagement improved from 61.50% in Cycle I to 84.75% in Cycle II, indicating that PjBL effectively enhanced students’ participation, collaboration, and critical thinking skills. Teacher performance also improved from 70.25% in Cycle I to 88.10% in Cycle II. These findings demonstrate that the Project Based Learning model is effective in improving student learning outcomes in Islamic Education, as it encourages active learning, problem-solving, and meaningful learning experiences. Therefore, PjBL is recommended as an innovative instructional approach to enhance student achievement and engagement in Islamic Education at the elementary school level.